Communication Skill Training For Cadres Through Education and Simulation - Suryani Maryam (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Cadres are one of the elements that have an important role in public health services. Effective and efficient communication skills are necessary for the actions of cadres who contact often with the community, such as during posyandu services and counseling. The goal of this service is to enhance the communicative and listening abilities of cadres at the Integrated Services Post (Posyandu) when they are interacting with the community. They will practice in developing their communication skills both verbal and non verbal communication. The main target of this activity is Posyandu cadres in Menteng Dalam Village. The method used in this training are : instruction, simulations, and mentorship. Community service activities using a combination of these methods can increase the knowledge and skills of Posyandu cadres in giving service and conducting health education in the community. The results of the activity include an increase in the knowledge and skills of effective communication of cadres. It is recommended that cadres receive specialized training on how to disseminate health information through media promotion and health education. Keywords : Communication skill, Training, Cadres.